Modeling Research and Test Verification of the Seismic Response of a Multistage Series Liquid Tank - Xiaoguang Yao; Lijun Meng; Peng Chu; Liang Yao (Shock and Vibration)
Liquid storage tanks are lifeline structures and strategically very important. Heavy damages or even collapse of these facilities subjected to strong earthquakes may cause disastrous consequences. In this paper, the seismic response of a multistage series liquid storage tank was simulated by a finite element method and verified by a scaled-down experiment. The structural flexibility of the tank and the liquid-structure coupling characteristics between the liquid and tank wall were considered in the research. A multimass-block and spring model was employed to be equivalent to the longitudinal vibration of the liquid in the storage tank. The relationships between the connection springs and the elements of the stiffness matrix were explicitly deduced. The seismic response analysis of a four-stage series liquid tank was carried out, and the acceleration response, the stress response of the tank, and the vertical vibration of the liquid were obtained. The experimental results are in good agreement with the simulation results, which verifies the effectiveness of the modeling method in this paper.